Zombies - Peabody, Erin (Peabody, Erin. Behind the legend., 2017)
"Are undead, brain-hungry zombies real, or just a myth? You decide with this new book in the nonfiction series, Behind the Legend! Behind the Legend looks at creatures and monsters throughout history and analyzes them through a scientific, mythbusting lens, debating whether or not the sightings and evidence provided are adequate proof of their existence. In Zombies, readers learn about all the stories and "proof" of them, from accounts in history and literature of people being made into zombies, including from Mesopotamia, Haiti, and America, as well as our own modern understanding of zombies' qualities. It also discusses additional history about the monsters, such as how zombies became major figures in popular culture, more recent understandings, and theories on how people turn into zombies. Complete with engaging anecdotes, interesting sidebars, and fantastic illustrations, kids won't want to put this book down!"--